Effect Of Filler On Weld Metal Structure Of AA6061 Aluminum Alloy By Tungsten Inert Gas Welding - M., Ishak; N. F. M., Noordin; A. S. K., Razali; L. H., Shah; F. R. M., Romlay (Universiti Malaysia Pahang, 2015)
Innovative welding technology in joining aluminum alloys in the automobile, aviation, aerospace and marine industries would achieve weight reduction and high specific strength as well as increasing fuel efficiency and reducing environmental pollution. This study presents an appropriate welding filler to join similar AA6061 aluminum alloys using the tungsten inert gas (TIG) process. The TIG welding of AA6061 was butt joined with three different fillers: ER5356 (4.5–6% Mg), ER4043 (4.5–6% Si) and ER4047 (11–13% Si). The experiments were conducted in order to investigate the macrostructure and microstructure of the samples as well as the mechanical properties. The effect of preheating was also investigated. The effects of the different fillers used on the weld joints were analyzed by their visual appearance, microstructures, hardness and strength. It was found that welding by using filler ER5356 produced a finer grain size and the highest strength of 171.53 MPa compared to the weld joints using fillers ER4047 and ER4047 with values of 167.34 MPa and 168.03 MPa, respectively.